THE EFFECT OF LIQUIDITY, ASSET STRUCTURE AND SALES GROWTH ON THE CAPITAL STRUCTURE AND ITS IMPLICATIONS FOR SHARE PRICES MODERATED BY BI INTEREST RATES - Dede Yusuf; Jaja Suteja; Atang Hermawan (SEAN Institute, 2023)
This study aims to influence liquidity, asset structure and sales growth on the capital structure and its implications for share prices moderated by BI interest rates. This research uses a quantitative approach. The tool used in this study is multiple regression analysis where there is a relationship between independent variables and dependent variables. The results of this study stated that liquidity, asset structure and sales growth significantly affected the capital structure of manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018. Liquidity has asignificantly affectscapital structure of manufacturing companies listed on the Indonesia Stock Exchange. the greater the liquidity, the higher the ability to pay off its short-term debt to manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018. Asset structure affects the capital structure of manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018. Sales growth affected the capitalmanufacturing companies' capital structureonesia Stock Exchange from 2009 to 2018. The capital structure affects the price of manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018. The capital structure affects the share price moderated by BI interest rates on manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2018.